Father, Womb, Blood: Apollo’s embryological theory, the ethics of revenge, and the supposed exclusion of women in Aischylos’ Eumenides - Tralau, Johan (Literatūra, 2019)
In Aischylos’ Eumenides, Apollo intimates a theory according to which the father is the sole genetic parent of the child. The status of this conception, and whether it is depicted as an outlandish idea, has been much and inconclusively discussed. This paper considers a neglected piece of evidence: Apollo’s use of the very unusual word αὐτάδελφον when addressing Hermes. In light of the Greeks’ awareness of this etymology as well as the other instances of this rare word in tragedy, the author argues that Aischylos’ text highlights the etymological connection to δελφύς, the womb, thus evoking the role of the mother. This suggests that Aischylos subtly lets his, and Apollo’s, language rebel against the notion of merely paternal kinship, and the concomitant ideas about revenge, retaliation and children’s obligations to their parent.
Keywords: Aischylos; ἀδελφός; αὐτάδελφος; womb; mother; father